2020
DOI: 10.1111/and.13554
|View full text |Cite
|
Sign up to set email alerts
|

Lycium barbarum polysaccharide protects against ethanol‐induced spermiotoxicity and testicular degeneration in Immp2l +/− mice

Abstract: Studies have indicated that high levels of ethanol exposure impaired spermatogenesis in mice. However, the effects of chronic and low‐dose alcohol consumption on susceptible populations remain unclear. The previous studies have confirmed that Immp2l mutant mice (Immp2lTg(Tyr)979Ove or Immp2l−/−) suffered from increased levels of oxidative stress(OS) and male infertility, heterozygous lmmp2l mice (Immp2l+/−) showed no altered ROS levels under physiological condition. Lycium barbarum polysaccharide (LBP) signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 26 publications
(33 reference statements)
1
13
0
Order By: Relevance
“…An earlier truncated Immp2l mouse model ( Immp2l Tg(Tyr)979Ove ) first reported in 2008 by Lu et al [ 3 ] and which subsequently became the subject of at least 18 additional publications [ 3 , 28 , 29 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ] presented with increased ROS and numerous associated oxidative stress phenotypes. Furthermore, this earlier truncated Immp2l Tg(Tyr)979Ove mouse had a complex genotype ( Immp2l Tg(Tyr)979Ove ) inclusive of an intragenic deletion in Immp2l and expressed a largely intact yet truncated form of Immp2l that made it difficult to determine the precise origin of the increased levels of ROS and associated oxidative stress phenotypes [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An earlier truncated Immp2l mouse model ( Immp2l Tg(Tyr)979Ove ) first reported in 2008 by Lu et al [ 3 ] and which subsequently became the subject of at least 18 additional publications [ 3 , 28 , 29 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ] presented with increased ROS and numerous associated oxidative stress phenotypes. Furthermore, this earlier truncated Immp2l Tg(Tyr)979Ove mouse had a complex genotype ( Immp2l Tg(Tyr)979Ove ) inclusive of an intragenic deletion in Immp2l and expressed a largely intact yet truncated form of Immp2l that made it difficult to determine the precise origin of the increased levels of ROS and associated oxidative stress phenotypes [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the earlier truncated Immp2l Tg(Tyr)979Ove mouse was developed on a blind background strain of mice (FVB/N) that made it unsuitable for behavioural examination [ 3 ]. As our primary interest is the aetiology of ASD-relevant behaviours, we developed the new Immp2l KD −/− KO mouse strain on a C57BL/6J background [ 53 ] that we demonstrate is devoid of Immp2l peptidase activity yet exhibits none of the overt oxidative stress-related phenotypes reported for the earlier truncated Immp2l Tg(Tyr)979Ove mouse model [ 3 , 28 , 29 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our results revealed that immuno-expression of caspase 3, an executioner of cell apoptosis increased significantly in testis of treated groups relative to the control, which implies increased apoptosis due to the treatments. Additionally, previous studies have reported apoptosis in the testis of animals that are diabetic [ 44 , 65 ], exposed to alcohol [ 66 , 67 ], and treated with cART [ 47 , 68 ]. Further, a significant decrease in the number of germ cells expressing Ki-67 but with strong staining intensity was recorded in the treated groups suggesting a disruption of germ cell proliferation and spermatogenesis dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…LBP ( Lycium barbarum polysaccharides) has biological activities especially regarding reproductive system protection, such as enhancing immune function, antioxidation, reducing inflammation, and apoptosis 30 . Studies have shown that the protective effect of LBP on germ cells is mainly associated with the ability of LBP to enhance antioxidation, thereby reducing the level of oxidative stress and inhibiting apoptosis 31–33 . It has been reported that LBP mainly plays an anti‐inflammatory, immunomodulatory, antioxidant, and anti‐apoptotic role through the nuclear factor‐κ B, PI3K‐AKT–mTOR, p38‐MAPK, WNT‐β‐catenin, PI3K‐AKT‐GSK‐3β, and MyD88 signaling pathways 34 .…”
Section: Introductionmentioning
confidence: 99%
“…30 Studies have shown that the protective effect of LBP on germ cells is mainly associated with the ability of LBP to enhance antioxidation, thereby reducing the level of oxidative stress and inhibiting apoptosis. [31][32][33] It has been reported that LBP mainly plays an antiinflammatory, immunomodulatory, antioxidant, and anti-apoptotic role through the nuclear factor-κ B, PI3K-AKT-mTOR, p38-MAPK, WNTβ-catenin, PI3K-AKT-GSK-3β, and MyD88 signaling pathways. 34 However, it remains to be determined, whether LBP also reduces the expression of Fas/FasL signaling pathway proteins, which would result in a protective effect.…”
mentioning
confidence: 99%